Molecular epidemiology of methicillin-resistant Staphylococcus aureus in a burn unit from Brazil - Rodrigues, Marcus Vinicius Pimenta [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Riboli, Danilo Flávio Moraes [UNESP]; Rocha, Renata Silveira [UNESP]; Rocha, Cristiane [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Elsevier, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) poses a threat for patients in burn units. Studies that mix epidemiological designs with molecular typing may contribute to the development of strategies for MRSA control. We conducted a study including: molecular characterization of Staphylococcal Chromosome Cassette mecA (SCCmec), strain typing with pulsed field gel electrophoresis (PFGE) and detection of virulence genes, altogether with a case-case-control study that assessed risk factors for MRSA and for methicillin-susceptible S. aureus (MSSA), using S. aureus negative patients as controls. Strains were collected from clinical and surveillance cultures from October 2006 through March 2009. MRSA was isolated from 96 patients. Most isolates (94.8%) harbored SCCmec type III. SCCmec type IV was identified in isolates from four patients. In only one case it could be epidemiologically characterized as community-associated. PFGE typing identified 36 coexisting MRSA clones. When compared to MSSA (38 isolates), MRSA isolates were more likely to harbor two virulence genes: tst and lukPV. Previous stay in other hospital and admission to Intensive Care Unit were independent risk factors for both MRSA and MSSA, while the number of burn wound excisions was significantly related with the former (OR = 6.80, 95%CI = 3.54-13.07). In conclusion, our study found polyclonal endemicity of MRSA in a burn unit, possibly related to importing of strains from other hospitals. Also, it pointed out to a role of surgical procedures in the dissemination of MRSA strains. © 2013 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Molecular epidemiology; MRSA burn units; Risk factors; Staphylococcus aureus; amoxicillin plus clavulanic acid; cefepime; ciprofloxacin; clindamycin; gentamicin; imipenem; oxacillin; Panton Valentine leukocidin; penicillin binding protein 2a; toxic shock syndrome toxin 1; vancomycin; adult; aged; bacterial chromosome; bacterial strain; bacterial virulence; bacterium culture; bacterium isolate; bacterium isolation; Brazil; burn; burn unit; child; controlled study; excision; female; gene cassette; hospital admission; hospitalization; human; intensive care unit; major clinical study; male; methicillin resistant Staphylococcus aureus; methicillin susceptible Staphylococcus aureus; molecular epidemiology; nonhuman; preschool child; pulsed field gel electrophoresis; risk factor